MARKET PENETRATION TECHNIQUES FOR SMALL BUSINESSES IN NIGERIA: A CASE STUDY APPROACH (Journal of the Management Sciences, 2025)
This study explored market penetration techniques employed by small businesses in Delta State, Nigeria, focusing on pricing strategies, promotional activities, and distribution channels. Using a descriptive case study design, the research examined how these strategies impact market penetration. The study was conducted in three major cities—Warri, Asaba, and Sapele—representing the commercial, administrative, and semi-urban areas of Delta State. A sample of 150 participants, comprising small business owners and managers, was selected using a stratified random sampling technique. Data were collected via structured questionnaires distributed electronically using snowball sampling, leveraging networks through WhatsApp and email. The collected data were analyzed using descriptive statistics and multiple regression analysis, facilitated by SPSS software. The findings revealed that pricing strategies significantly enhance market penetration, with penetration pricing contributing the most (R² = 0.581). Promotional activities also play a critical role, with public relations strategies emerging as the most effective (R² = 0.511). Distribution channels significantly impact market access, with direct channels being the most influential (R² = 0.465), while e-commerce platforms show potential but remain underutilized due to infrastructural limitations. Hypothesis testing confirmed the significant influence of all three strategies on market penetration. These findings underscore the importance of adopting innovative strategies tailored to local market dynamics. Practical recommendations include adopting penetration pricing, leveraging digital marketing, and enhancing distribution infrastructure. Policymakers are urged to support small businesses through digital infrastructure development and financial incentives for marketing and distribution innovations. The study highlights the critical need for strategic management to ensure the sustainability and growth of small businesses in competitive markets.
Keywords: Market Penetration, Techniques; Small Businesses; Pricing Strategies; Promotional Activities, Distribution Channel; Nigeria